The role of lipid post–translational modification in plant developmental processes - Running, Mark P. (Frontiers in Plant Science, 2014)
Most eukaryotic proteins are post-translationally modified, and modification has profound effects on protein function. One key modification is the attachment of a lipid group to certain amino acids; this typically facilitates subcellular targeting (association with a membrane) and protein-protein interactions (by virtue of the large hydrophobic moiety). Most widely recognized are lipid modifications of proteins involved in developmental signaling, but proteins with structural roles are also lipid-modified. The three known types of intracellular protein lipid modifications are S-acylation, N-myristoylation, and prenylation. In plants, genetic analysis of the enzymes involved, along with molecular analysis of select target proteins, has recently shed light on the roles of lipid modification in key developmental processes, such as meristem function, flower development, polar cell elongation, cell differentiation, and hormone responses. In addition, while lipid post-translational mechanisms are generally conserved among eukaryotes, plants differ in the nature and function of target proteins, the effects of lipid modification on target proteins, and the roles of lipid modification in developmental processes.